2023
DOI: 10.1177/03946320231169175
|View full text |Cite
|
Sign up to set email alerts
|

Experimental study on the effect of luteolin on the proliferation, apoptosis and expression of inflammation-related mediators in lipopolysaccharide-induced keratinocytes

Abstract: Objective This study aimed at exploring the effects of luteolin on psoriasis-like cell model proliferation, apoptosis regulation and the expression of inflammation-related mediators. Methods A Cell Counting Kit-8 (CCK-8) assay was used to determine the survival rate of human immortalized keratinocytes (HaCaT cells) and normal human epidermal keratinocytes (NHEK cells) following stimulation with luteolin and lipopolysaccharide (LPS). Western blot and reverse transcription-quantitative polymerase chain reaction … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 27 publications
(37 reference statements)
0
3
0
Order By: Relevance
“…Finally, lipopolysaccharide (LPS), a component of the gram-negative bacterial wall that is known to induce inflammatory cytokine secretion by adipocytes and involved in keratinocyte stimulation in psoriasis, 15 , 16 did not stimulate any increase of IL-23 expression in human adipocytes in vitro ( Figure 4 ). All these results further suggest that the stimulatory effect of insulin on IL-23 expression by human adipocytes is selective and specific.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, lipopolysaccharide (LPS), a component of the gram-negative bacterial wall that is known to induce inflammatory cytokine secretion by adipocytes and involved in keratinocyte stimulation in psoriasis, 15 , 16 did not stimulate any increase of IL-23 expression in human adipocytes in vitro ( Figure 4 ). All these results further suggest that the stimulatory effect of insulin on IL-23 expression by human adipocytes is selective and specific.…”
Section: Resultsmentioning
confidence: 99%
“…Given the fact that lipopolysaccharide (LPS), a complex molecule of gram-negative bacteria cellular wall, can stimulate an inflammatory response in adipocytes 15 and keratinocytes, 16 we have compared the effects of insulin on adipocyte expression of IL-23 with those of LPS.…”
Section: Introductionmentioning
confidence: 99%
“…These cells release specific inflammatory mediators, such as tumor necrosis factor-alpha, IL-1, and IL-6, which subsequently drive keratinocyte proliferation. The release of these inflammatory mediators activates myeloid dendritic cells, prompting the secretion of IL-12 and IL-23 by naïve T cells, thus facilitating the differentiation of naïve T cells into T helper (Th)1 and Th17 cells [ 51 , 52 , 53 ]. A recent study highlighted correlations between psoriasis severity and TNF-α-related mitogen-activated protein kinase, NF-kB, and Janus kinase pathways [ 54 ].…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we demonstrated that GC inhibited the proliferation of HaCaT cells and induced their death. LPS is usually used for stimulating HaCaT cells to make an in vitro inflammation model [45][46][47]. LPS promotes the phosphorylation of JAK1 and STAT3, leading to increased cellular inflammation [45].…”
Section: Discussionmentioning
confidence: 99%